Structural and gas adsorption study of a two-dimensional copper-tetrazole based metal-organic framework - Pachfule, Pradip; Banerjee, Rahul (Current Science, 2011)
A new two-dimensional (2D) metal organic framework, Cu-1(4-TBA)(1)(DMBP)(1).DMF (Cu-TBA-3), has been synthesized under solvothermal condition from transition metal cation Cu(II), predesigned ligand 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and coligand 4,4'-dimethy1-2,2'-bipyridine (DMBP). The structure has been determined by single crystal X-ray crystallography which shows layered 2D structure with square shaped one-dimensional channels. Cu-TBA-3 shows 0.69 wt% H-2 (at 77 K, 1 atm) and 1.65 mmol/g CO2 (at 298 K, 1 atm) uptake.
Keywords: CO2 capture; Hydrogen storage; metal-organic frameworks; microporous materials

Control of porosity by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template for porous carbon synthesis - Pachfule, Pradip; Biswal, Bishnu P.; Banerjee, Rahul (Chemistry-A European Journal, 2012)
Herein, by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template, we report the synthesis, morphology, and gas adsorption properties of porous carbon synthesized by a nanocasting method at 1000 degrees C, in which furfuryl alcohol (FA) was used as a carbon source. By using IRZIFs with variable porosity as templates, we could achieve control over the carbon porosity and H-2 and CO2 uptake. The resultant microporous carbon C-70, synthesized by using ZIF-70 as the template, is the most porous (Brunauer-Emmett-Teller (BET) surface area 1510 m(2)g(-1)). Carbon C-68, synthesized by using ZIF-68, has moderate porosity (BET surface area 1311 m(2)g(-1)), and C-69, synthesized by using ZIF-69, has the lowest porosity in this series (BET surface area 1171 m(2)g(-1)). The porous carbons C-70, C-68, and C-69, which have graphitic texture, have promising H2 uptake capacities of 2.37, 2.15, and 1.96 wt%, respectively, at 77 K and 1 atm. Additionally, C-70, C-68, and C-69 show CO2 uptake capacities of 5.45, 4.98, and 4.54 mmolg(-1), respectively, at 273 K and 1 atm. The gas uptake trends shown by C-70, C-68, and C-69 clearly indicate the dependence of carbon porosity on the host template. Moreover, the as-synthesized carbons C-70, C-68, and C-69 show variable conductivity.
Keywords: Carbon; Hydrogen storage; metal-organic frameworks; microporous materials; zinc

Fluorinated metal-organic frameworks: advantageous for higher H-2 and CO2 adsorption or not? - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemistry-A European Journal, 2012)
The synthesis, structure, and gas adsorption properties of three new metalorganic frameworks (MOFs) designed from isonicotinic acid (INA) and its fluorinated analogue 3-fluoroisonicotinic acid (FINA) along with CoII as the metal center have been reported. Co-INA-1 ([Co3(INA)4(O)(C2H5OH)3][NO3].C2H5OH.3?H2O; INA=isonicotinic acid) and Co-INA-2 ([Co(INA)2].DMF) are structural isomers as are Co-FINA-1 ([Co3(FINA)4(O)(C2H5OH)2].H2O; FINA=3-fluoroisonicotinic acid) and Co-FINA-2 ([Co(FINA)2].H2O), but the most important thing to note here is that Co-INA-1 and Co-FINA-1 are isostructural as are Co-INA-2 and Co-FINA-2. The effect of partial introduction of fluorine atoms into the framework on the gas uptake properties of MOFs having similar structures has been analyzed experimentally and computationally in isostructural MOFs.
Keywords: cobalt; fluorine; Hydrogen storage; metal-organic frameworks; microporous materials; X-ray diffraction

Hydrolytic conversion of a metal-organic polyhedron into a metal-organic framework - Mallick, Arijit; Garai, Bikash; Diaz, David Diaz; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: cage compounds; crystal engineering; hydrophobic effect; metal-organic frameworks; Self-assembly

Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

Evolution of an adenine-copper cluster to a highly porous cuboidal framework: solution-phase ripening and gas-adsorption properties - Venkatesh, V.; Pachfule, Pradip; Banerjee, Rahul; Verma, Sandeep (Chemistry-A European Journal, 2014)
The synthesis and directed evolution of a tetranu-clear copper cluster, supported by 8-mercapto-N9-propyladenine ligand, to a highly porous three-dimensional cubic framework in the solid state is reported. The structure of this porous framework was unambiguously characterized by Xray crystallography. The framework contains about 62% solvent-accessible void; the presence of a free exocyclic amino group in the porous framework facilitates reversible adsorption of gas and solvent molecules. Oriented growth of framework in solution was also tracked by force and scanning electron microscopy studies, leading to identification of an intriguing ripening process, over a period of 30 days, which also revealed formation of cuboidal aggregates in solution. The elemental composition of these cuboidal aggregates was ascertained by EDAX analysis.
Keywords: cuboidal frameworks; gas adsorption; metal-organic frameworks; Ostwald ripening; solution-phase ripening

Mechanical downsizing of a gadolinium(iii)-based metal-organic framework for anticancer drug delivery - Kundu, Tanay; Mitra, Shouvik; Patra, Prasun; Goswami, Arunava; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2014)
A Gd-III-based porous metal-organic framework (MOF), Gd-pDBI, has been synthesized using fluorescent linker pDBI (pDBI=(1,4-bis(5-carboxy-1H-benzimidazole-2-yl)benzene)), resulting in a three-dimensional interpenetrated structure with a one-dimensional open channel (1.9x1.2nm) filled with hydrogen-bonded water assemblies. Gd-pDBI exhibits high thermal stability, porosity, excellent water stability, along with organic-solvent and mild acid and base stability with retention of crystallinity. Gd-pDBI was transformed to the nanoscale regime (ca. 140nm) by mechanical grinding to yield MG-Gd-pDBI with excellent water dispersibility (>90min), maintaining its porosity and crystallinity. In vitro and in vivo studies on MG-Gd-pDBI revealed its low blood toxicity and highest drug loading (12wt%) of anticancer drug doxorubicin in MOFs reported to date with pH-responsive cancer-cell-specific drug release.
Keywords: ball-milling; doxorubicin; drug delivery; metal-organic frameworks; nanocarriers

Two-in-one: inherent anhydrous and water-assisted high proton conduction in a 3D metal-organic framework - Nagarkar, Sanjog S.; Unni, SreeKuttan M.; Sharma, Amitosh; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2014)
The development of solid-state proton-conducting materials with high conductivity that operate under both anhydrous and humidified conditions is currently of great interest in fuel-cell technology. A 3Dmetal-organic framework (MOF) with acid-base pairs in its coordination space that efficiently conducts protons under both anhydrous and humid conditions has now been developed. The anhydrous proton conductivity for this MOF is among the highest values that have been reported for MOF materials, whereas its water-assisted proton conductivity is comparable to that of the organic polymer Nafion, which is currently used for practical applications. Unlike other MOFs, which conduct protons either under anhydrous or humid conditions, this compound should represent a considerable advance in the development of efficient solid-state proton-conducting materials that work under both anhydrous and humid conditions.
Keywords: conducting materials; fuel cells; metal-organic frameworks; porous materials; proton conduction

Single crystal-to-single crystal site-selective postsynthetic metal exchange in a Zn-MOF based on semi-rigid tricarboxylic acid and access to bimetallic MOFs - Bajpai, Alankriti; Chandrasekhar, Pujari; Govardhan, Savitha; Banerjee, Rahul; Moorthy, Jarugu Narasimha (Chemistry-A European Journal, 2015)
The metal ions in a neutral Zn-MOF constructed from tritopic triacid H3L with inherent concave features, rigid core, and peripheral flexibility are found to exist in two distinct SBUs, that is, 0D and 1D. This has allowed site-selective postsynthetic metal exchange (PSME) to be investigated and reactivities of the metal ions in two different environments in coordination polymers to be contrasted for the first time. Site-selective transmetalation of Zn ions in the discrete environment is shown to occur in a single crystal-to-single crystal (SCSC) fashion, with metal ions such as Fe3+, Ru3+, Cu2+, Co2+, etc., whereas those that are part of 1D SBU sustain structural integrity, leading to novel bimetallic MOFs, which are inaccessible by conventional approaches. To the best of our knowledge, site-selective postsynthetic exchange of an intraframework metal ion in a MOF that contains metal ions in discrete as well as polymeric SBUs is heretofore unprecedented.
Keywords: coordination polymers; metal-exchange; metal-organic frameworks; Metathesis; X-ray crystallography

Versatile Cu-II metal-organic framework exhibiting high gas storage capacity with selectivity for CO2: conversion of CO2 to cyclic carbonate and other catalytic abilities - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Sen Gupta, Sayam; Bharadwaj, Parimal K. (Chemistry-A European Journal, 2016)
A linear tetracarboxylic acid ligand, H4L, with a pendent amine moiety solvothermally forms two isostructural metal-organic frameworks (MOFs) L-M (M=Zn-II, Cu-II). Framework L-Cu can also be obtained from L-Zn by post- synthetic metathesis without losing crystallinity. Compared with L-Zn, the L-Cu framework exhibits high thermal stability and allows removal of guest solvent and metal-bound water molecules to afford the highly porous, L-Cu. At 77K, L-Cu absorbs 2.57wt% of H-2 at 1bar, which increases significantly to 4.67wt% at 36bar. The framework absorbs substantially high amounts of methane (238.38cm(3)g(-1), 17.03wt%) at 303K and 60bar. The CH4 absorption at 303K gives a total volumetric capacity of 166cm(3)(STP)cm(-3) at 35bar (223.25cm(3)g(-1), 15.95wt%). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0wt% of CO2 to be absorbed at 1bar and 273K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, L-Cu shows pronounced selectivity for CO2 absorption over CH4, N-2, and H-2 at 273K. The absorbed CO2 can be converted to value-added cyclic carbonates under relatively mild reaction conditions (20bar, 120 degrees C). Finally, L-Cu is found to be an excellent heterogeneous catalyst in regioselective 1,3-dipolar cycloaddition reactions (click reactions) and provides an efficient, economic route for the one-pot synthesis of structurally divergent propargylamines through three-component coupling of alkynes, amines, and aldehydes.
Keywords: click reactions; CO2 absorption; cyclic carbonate; heterogeneous catalysis; metal-organic frameworks

Single cell fabrication towards the realistic evaluation of a CNT-strung ZIF-derived electrocatalyst as a cathode material in alkaline fuel cells and metal-air batteries - Aiyappa, Harshitha Barike; Bhange, Siddheshwar N.; Sivasankaran, Vijitha P.; Kurungot, Sreekumar (ChemElectroChem, 2017)
The development of an electrocatalyst possessing all the vital requisites of an ideal electrode material, such as high porosity, high conductivity, and high intrinsic electrochemical activity, holds a decisive key in determining the activity of the triplephase boundary in many energy devices like fuel cells and metal-air battery systems. In the present work, highly porous cobalt-based ZIFs are strung along the highly conducive CNT backbone by using a simple one-pot technique at room temperature, which is then utilized to derive a porous, corrosion-resistant, Co nanoparticle-embedded electrocatalyst. Herein, for the first time, the single cell performance of the Co-ZIF-67-derived electrocatalyst has been evaluated by fabricating membrane electrode assemblies of alkaline exchange membrane fuel cell (AEMFC) and zinc-air battery (ZAB) systems. A maximum power density of 296 mW/cm(2) (vs. 317 mW/cm(2) for 40 wt.% Pt/C) and 60 mW/cm(2) (vs. 64 mW/cm(2) for 40 wt.% Pt/C) in the single cells of ZAB and AEMFC systems, respectively, establishes the practical proficiency of the homemade electrocatalyst for cathode applications during realistic system-level validations.
Keywords: Batteries; Carbon nanotubes; Composite materials; fuel cells; metal-organic frameworks

Crystal engineering: an outlook for the future - Nangia, Ashwini K.; Desiraju, Gautam R. (Angewandte Chemie-International Edition, 2019)
Crystal Engineering has traditionally dealt with molecular crystals. It is the understanding of intermolecular interactions in the context of crystal packing and in the utilization of such understanding in the design of new solids with desired physical and chemical properties. We outline here five areas which come under the umbrella of Crystal Engineering and where we feel that a proper planning of research efforts could lead to higher dividends for science together with greater returns for humankind. We touch on themes and domains where science funding and translation efforts could be directed in the current climate of a society that increasingly expects applications and utility products from science and technology. The five topics are: 1)pharmaceutical solids; 2)industrial solid state reactions; 3)mechanical properties with practical applications; 4)MOFs and COFs framework solids; 5)new materials for solar energy harvesting and advanced polymers.
Keywords: crystal engineering; metal-organic frameworks; pharmaceutical solids; solar energy; solid-state reactions

2D layered nanomaterials as fillers in polymer composite electrolytes for lithium batteries - Vijayakumar, Vidyanand; Ghosh, Meena; Asokan, Kiran; Sukumaran, Santhosh Babu; Kurungot, Sreekumar; Mindemark, Jonas; Brandell, Daniel; Winter, Martin; Nair, Jijeesh Ravi (Advanced Energy Materials, 2023)
Polymer composite electrolytes (PCEs), i.e., materials combining the disciplines of polymer chemistry, inorganic chemistry, and electrochemistry, have received tremendous attention within academia and industry for lithium-based battery applications. While PCEs often comprise 3D micro- or nanoparticles, this review thoroughly summarizes the prospects of 2D layered inorganic, organic, and hybrid nanomaterials as active (ion conductive) or passive (nonion conductive) fillers in PCEs. The synthetic inorganic nanofillers covered here include graphene oxide, boron nitride, transition metal chalcogenides, phosphorene, and MXenes. Furthermore, the use of naturally occurring 2D layered clay minerals, such as layered double hydroxides and silicates, in PCEs is also thoroughly detailed considering their impact on battery cell performance. Despite the dominance of 2D layered inorganic materials, their organic and hybrid counterparts, such as 2D covalent organic frameworks and 2D metal-organic frameworks are also identified as tuneable nanofillers for use in PCE. Hence, this review gives an overview of the plethora of options available for the selective development of both the 2D layered nanofillers and resulting PCEs, which can revolutionize the field of polymer-based solid-state electrolytes and their implementation in lithium and post-lithium batteries.
Keywords: 2D materials; clay minerals; covalent organic frameworks; metal-organic frameworks; MXene; polymer composite electrolyte; solid-state batteries

Metal-organic framework-derived mesoporous B-doped CoO/Co@N-doped carbon hybrid 3D heterostructured interfaces with modulated cobalt oxidation states for alkaline water splitting - Cha, Dun Chan; Singh, Thangjam Ibomcha; Maibam, Ashakiran; Kim, Tae Hyeong; Nam, Dong Hwan; BabaRao, Ravichandar; Lee, Seunghyun (Small, 2023)
Heteroatom-doped transition metal-oxides of high oxygen evolution reaction (OER) activities interfaced with metals of low hydrogen adsorption energy barrier for efficient hydrogen evolution reaction (HER) when uniformly embedded in a conductive nitrogen-doped carbon (NC) matrix, can mitigate the low-conductivity and high-agglomeration of metal-nanoparticles in carbon matrix and enhances their bifunctional activities. Thus, a 3D mesoporous heterostructure of boron (B)-doped cobalt-oxide/cobalt-metal nanohybrids embedded in NC and grown on a Ni foam substrate (B-CoO/Co@NC/NF) is developed as a binder-free bifunctional electrocatalyst for alkaline water-splitting via a post-synthetic modification of the metal-organic framework and subsequent annealing in different Ar/H-2 gas ratios. B-CoO/Co@NC/NF prepared using 10% H-2 gas (B-CoO/Co@NC/NF [10% H-2]) shows the lowest HER overpotential (196 mV) and B-CoO/Co@NC/NF (Ar), developed in Ar, shows an OER overpotential of 307 mV at 10 mA cm(-2) with excellent long-term durability for 100 h. The best anode and cathode electrocatalyst-based electrolyzer (B-CoO/Co@NC/NF (Ar)(+)//B-CoO/Co@NC/NF (10% H-2)(-)) generates a current density of 10 mA cm(-2) with only 1.62 V with long-term stability. Further, density functional theory investigations demonstrate the effect of B-doping on electronic structure and reaction mechanism of the electrocatalysts for optimal interaction with reaction intermediates for efficient alkaline water-splitting which corroborates the experimental results.
Keywords: 3D heterostructures; B-doped metal-oxides; electrocatalysts; hydrogen evolution reactions; metal-organic frameworks; oxygen evolution reactions

Atmospheric-pressure continuous-flow methane oxidation to methanol and acetic acid using H2O2 over the Au-Fe catalyst - Jagtap, Anuradha V.; Kumar, Pawan; Gupta, Sharad; Nagendra, Abharana; Jha, Shambhu Nath; Bhattacharyya, D.; Ajithkumar, Thalasseril G.; Vinod, C. P. (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: CO oxidation; HIGHLY SELECTIVE OXIDATION; metal-organic frameworks